Moving From Windows to Linux
Moving from Windows to Linux, Second Edition is a step-by-step walk through the transition from Windows to Linux. This completely updated version of the best-selling book teaches Windows users how to make their PC a Linux PC. It covers the latest in Linux distributions, and provides Windows users with the information they need to choose the one that will best suit their needs. From there, the book works through the transition from Windows to SuSE Linux 9.3, leveraging what Windows users already know, and applying that knowledge to Linux. The transition from applications such as Microsoft Word, Microsoft Office and Adobe Photoshop to their Linux counterparts KWord, Open Office, and GIMP are treated thoroughly and made easy. Real-world, hands-on examples and troubleshooting problems are also included. After reading through the book, any knowledgeable user of Windows will be able to set up, maintain, and utilize all aspects of a Linux PC.